A novel multiple emulsion enhanced immunity via its biomimetic delivery approach. Issue 33 (9th July 2020) - Zou, Yongjuan; Wu, Nan; Miao, Chunyu; Yue, Hua; Wu, Jie; Ma, Guanghui
Abstract : A special emulsion with biomimetic structural dynamic properties was fabricated, inducing efficient vaccine–cell interaction and robust immunity. Abstract : To generate effective immunity post-vaccination, antigens need to be effectively captured and taken up by antigen-presenting cells (APCs) as a prerequisite. Biomimetic designs that mimic natural pathogen-like properties have provided platforms for antigen delivery. However, the structural dynamic properties of pathogens leading to their efficient internalization have been neglected in most platforms. Herein, we redesigned a special multiple emulsion with chitosan hydrogel nanoparticles inside, mimicking the configurational flexibility and deformational flexibility of pathogens. With the assistance of chitosan-antigen particles, the novel emulsion exhibited amplified deformability and the vaccine–cell contact zone was increased. Additionally, its configurational transitions, which offered sustained exposure of sheltered uptake signals including antigens and stimulator chitosan during endocytosis, resulted in efficient antigen delivery to APCs. Prolonged antigen depot effect, versatile antigen presentation, multiple immunocyte activation, and marked adjuvant-sparing effects were achieved as compared with those in the control groups. As a result, the intracellular emulsion formulation robustly induced both humoral and cellular immunity, especially CTL response, against the foot-and-mouth disease virus (FMDV) with improved biosafety. Our study highlights the positive impact of biomimetic structural dynamic properties on robust vaccine–cell interactions and provides a promising FMDV vaccine candidate.